DIGITALIZATION OF CROSS-BORDER COOPERATION IN CRIMINAL MATTERS AT THE LEVEL OF THE EUROPEAN UNION - Bugarski, Tatjana; Pisarić, Milana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
It is assumed that the use of information technologies in the judicial system could contribute not only to the increase in the efficiency of the work of the competent authorities and the rationalization of criminal proceedings and individual procedural actions, but that it could also have such an impact on the procedures of cross-border judicial cooperation between the competent authorities of different countries. At the level of the European Union, in the last fifteen years, there has been a strategic commitment towards the creation of European electronic justice, and the concept of cooperative digital justice has been developing recently. The concept also received a legal basis in 2023 with the adoption of Regulation on the digitization of judicial cooperation and access to justice in cross-border civil, commercial and criminal matters. This paper presents the origin and development of the ideas that led to the Regulation and analyzes the legal framework, with an emphasis on cooperation in criminal matters. Also, the paper pays attention to a special form of cross-border cooperation in criminal matters, which is participation in court proceedings via video-conference link or other technologies for remote communication, when individual participants in the proceedings are located on the territory of different member states, an increasingly certain modification of criminal proceedings in the environment of the growing use of information technologies.